Automated code-checking as a driver of BIM adoption - J. P. Poças Martins (2010)
With the scarcity of land supply, complex high-rise buildings of more than 50 storeys Information management in the construction industry is inefficient when compared with other industrial activities. Unlike other productive activities, the construction industry is yet to develop standard formats for the representation of its products, which would allow its participants to communicate efficiently and, in some cases, automatically. Several different information models-(BIM) that represent building products partially or as a whole have been developed over the last decades. Their adoption by the community of users has been, however, scarce. It is believed that the dissemination and adoption of these models throughout the construction industry is hindered by a cooperation problem: the cumulative benefits derived from widespread BIM adoption are clearly larger than those that can be achieved through individual adoption, while the initial direct and indirect costs are considerable. The incentives for single users to change work their processes are therefore modest. In this context, automated code checking performed upon designs that follow standard representation formats is regarded not as an end in itself, but rather as a demonstration of the immediate benefits that can be obtained by the users who voluntarily adopt this kind of information technology. In this paper, an information model and an application developed at FEUP are briefly presented. These tools perform automated code-checking of domestic water systems for compliance with the main national regulations. Automated code-checking should not only provide advantages due to simplified work processes, but it should also motivate users to adopt building information models, especially in the early stages of the construction process.